The Need for Culturally-Tailored Smartphone Applications for Weight Control - Stephen Coughlin; Dale Hardy; Lee Caplan (Georgia Southern University, 2016)
Background: Approximately 35% of U.S. adults are obese, and this rate is expected to increase by almost 50% by 2030. New media such as smartphone applications (apps) provide a useful and low-cost way to disseminate weight control information. For many culturally distinctive population subgroups, however, there is currently an absence of research-tested smartphone apps for weight control. Methods: In this commentary, we highlight the need for culturally tailored smartphone apps for weight control and offer recommendations for further research by providing two specific examples: 1) the characteristic dietary patterns and absence of smartphone apps for weight loss for Hispanic Americans, in English and Spanish, and 2) and need for smartphone apps for weight loss for Brazilian Americans, including those who speak Portuguese. Results: Smartphone apps can be an effective intervention for improving diet and nutrition, encouraging physical activity, and reducing obesity, but few randomized controlled trials have been conducted of stand-alone smartphone apps for weight loss that focus primarily on self-monitoring of diet and physical activity. Further, there have been no published studies of apps for promoting healthy diet, better nutrition, increasing levels of physical activity, and weight loss among Hispanic Americans or Brazilian Americans. Conclusions: Low-cost, effective e-Health interventions (healthcare practices supported by electronic processes) are needed to promote physical activity, healthy eating, and weight control in culturally distinctive subgroups of the population. For weight loss, apps should be developed by use of evidence-based approaches that relate to behavioral theories. Additional public health research is needed to identify low-cost, effective strategies for weight loss for people who have varying levels of health literacy, and for non-English speakers. Culturally tailored e-Health interventions for weight control are more likely to address the needs of individuals and increase their motivation to engage in health promoting behaviors.